Monetary Policy, Monetary Areas, and Financial Development with Electronic Money - Arnone, Marco (IMF Working Papers; Working Paper, 2004)
Electronic money (e-money), as a network good, could become an important form of currency in the future. Such a development could affect monetary policy effectiveness. If an increased use of e-money substantially limits the demand for central bank reserves, this limitation would require changes in the central bank operational target and a closer coordination of monetary and fiscal policies. Also, the optimal size of monetary unions would be different. However, the current level of e-money use does not seem to pose a threat to the stability of the financial system. Thus, central banks can successfully implement the objectives of monetary policy.